Stigma Partai dan Presentasi Diri Para Politisi Pelaku Tindak Pidana Korupsi - Lely Arrianie (Jurnal Communicate, 2015)
Election of powerful politicians to parliament as leaving a question mark after powerful politicians captivated politicians who incidentally is a former student organizations and youth activists who previously gave great hope to change the face of parliament and the bureaucracy in Indonesia. When the alleged or suspected, the public and even linking them with the party’s fault, and it displays the party seems to be a stigma corrupt party, even if the perpetrator is an individual of the party. This research was conducted with the phenomenological approach and interaction with the dramaturgical symbolic and interpretive qualitative analysis. This study is actually able to provide implications for institutions to organize and put anyone in the position of the suspect and his or attached a stigma to be treated fairly in comparison to what is experienced by those who have similar status, but they are not of the elite. Stigma of political party organization which is the effect of the enactment of the top cadres and the status of the suspect or his party elite or less will be able to degrade the party.